Simulated Aging of Metal Tritides by Ball Milling Induced Gas Incorporation. (17th February 2023) - Olson, Dustin; Shanahan, Kirk; Rai, Binod; Hitchcock, Dale; Housley, Catherine; Larsen, George
Abstract: The study of tritium aging effects on materials requires a significant time commitment as a consequence of its 12.3-year half-life, making developmental studies prohibitively difficult and expensive. However, detailed knowledge of long-term aging effects is critical to the development of structural and storage materials for future fusion reactor technologies. As a result, multiple approaches to simulated aging effects have been investigated. We report a method of simulated tritium aging achieved though the incorporation of trapped gases via high-energy ball milling of LaNi4.25 Al0.75 alloy storage material. Experimental results verify the presence of trapped gases by a combination of temperature programmed desorption and LECO chemical analysis. Following gas incorporation, we find that many of the degraded hydrogen sorption properties found in aged storage materials are reproduced by the ball milled powders.